Implementasi Pendidikan Agama Islam Pada Pasien Rehabilitasi Narkoba di Yayasan Rumah Sehat Harapan Kelurahan Pahlawan Kecamatan Binjai Utara - Juwanda Pranata Wijaya, Ahmad Fuadi, Marhan Hasibuan (Khazanah : Journal of Islamic Studies, 2023)
Drug abuse is a complex problem and has such a large and broad impact on the lives of individual humans. Such problems need guidance given to each individual both in terms of religion and general knowledge. One of the places for education of drug abusers is in the rehabilitation center. Religious counseling aims to get closer to the Creator, to be aware of the mistakes that have been made so that they do not repeat the mistakes that have been made, and to create self-confidence for the residents and to be able to change them into better human beings. This study aims to: (1) determine the implementation of religious education in drug residents. (2) To describe and analyze the impact of Islamic religious education on drug-using rehabilitation patients. The research method used is a qualitative approach. Data collection techniques by way of observation, interviews, and documentation. Analysis techniques flow chart analysis. The results showed: (1) researchers found the success of Islamic religious education to increase self-confidence and good character for residents, with religious activities such as praying 5 times a day and other learning.